2020
DOI: 10.3389/fonc.2020.595789
|View full text |Cite
|
Sign up to set email alerts
|

Histological Characteristics and Early-Stage Diagnosis Are Associated With Better Survival in Young Patients With Epithelial Ovarian Cancer: A Retrospective Analysis Based on Surveillance Epidemiology and End Results Database

Abstract: PurposeTo analyze the potential prognostic factors of epithelial ovarian cancer (EOC) in women aged under 35 compared to those aged 60–79.MethodsCases were retrospectively obtained from SEER database. Clinical characteristics, such as race, histological type, AJCC stage, laterality of tumors, CA125 results, and surgical strategies, were analyzed in < 35 years group and 60–79 years group. Kaplan-Meier survival curves were used to evaluate overall survival (OS) and cause-specific survival (CSS). Cox propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Age, tumor factors (grade, histologic type, presence of LVSI or molecular factors such as abnormal oncogene expressions or gene mutations) and surgical factors such as execution of lymphadenectomy have been reported to determine the prognosis of stage I EOC [2,4,[8][9][10]. Of those, only the surgical factors can be changed and improved.…”
Section: Discussionmentioning
confidence: 99%
“…Age, tumor factors (grade, histologic type, presence of LVSI or molecular factors such as abnormal oncogene expressions or gene mutations) and surgical factors such as execution of lymphadenectomy have been reported to determine the prognosis of stage I EOC [2,4,[8][9][10]. Of those, only the surgical factors can be changed and improved.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of stage III and IV patients is generally poor and mainly depends on the size of intraperitoneal metastases [ 24 ]. As stage progresses, the risk of death increases [ 25 , 26 ]. A large retrospective cohort study based on the SEER database suggested that mortality in patients with stage III–IV ovarian cancer is as high as 10% in 1 year [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate is related to the stage of the disease at the diagnosis. In patients diagnosed with advanced stage III-IV ovarian cancer, the 5-year survival rate is about 30%, whereas in those diagnosed at an early stage the 5-year survival rate is about 90% [15][16][17] . Therefore, it seems worthwhile to diagnose ovarian cancer at an early stage [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Unnecessary surgical procedures results from inadequate diagnostic tools preoperatively. Different laboratory markers, imagination methods and clinical parameters were presented for identifying malignancy potential of an adnexal mass [16] .…”
Section: Introductionmentioning
confidence: 99%